Apert syndrome: A rare anomalad - Himanshi Aggarwal; Saumyendra Vikram Singh; Pradeep Kumar (Wolters Kluwer Medknow Publications, 2014)
Apert syndrome is a developmental malformation characterized by craniosynostosis, a cone shaped calvarium, midface hypoplasia, pharyngeal attenuation, ocular manifestations and syndactyly of the hands and feet. The complex craniofacial and systemic deformities seen in Apert syndrome mandate a multidisciplinary approach to improve the quality of life of patients. This paper presents the case of a 27-year-old male patient who presented with the complaints of malaligned teeth, difficulty in chewing food, facial deformity along with syndactyly of the hands and toes, and was diagnosed as a case of Apert syndrome.